2011
DOI: 10.1682/jrrd.2010.11.0213
|View full text |Cite
|
Sign up to set email alerts
|

Assessment technique for computer-aided manufactured sockets

Abstract: Abstract-This article presents an assessment technique for testing the quality of prosthetic socket fabrication processes at computer-aided manufacturing facilities. The assessment technique is potentially useful to both facilities making sockets and companies marketing manufacturing equipment seeking to assess and improve product quality. To execute the assessment technique, an evaluator fabricates a collection of test models and sockets using the manufacturing suite under evaluation, then measures their shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The present study has shown that residuum spatial alignment can be achieved with minimal input from a user of the developed software. Recently, Zachariah et al and Sanders and Severance produced and demonstrated quantitative techniques to compare sockets, both to assess errors in CAD/CAM socket production and to monitor longitudinal residual-limb evaluation [36][37]. It was shown that weighted surface normal/mean absolute error algorithms performed better than ICP when aligning residuum shape models from repeat scans over a longitudinal period (for tracking changes over time).…”
Section: Discussionmentioning
confidence: 99%
“…The present study has shown that residuum spatial alignment can be achieved with minimal input from a user of the developed software. Recently, Zachariah et al and Sanders and Severance produced and demonstrated quantitative techniques to compare sockets, both to assess errors in CAD/CAM socket production and to monitor longitudinal residual-limb evaluation [36][37]. It was shown that weighted surface normal/mean absolute error algorithms performed better than ICP when aligning residuum shape models from repeat scans over a longitudinal period (for tracking changes over time).…”
Section: Discussionmentioning
confidence: 99%
“…Shape deviation was analysed further using a 'height' deviation, presenting the surfacesurface normal deviation data following the visualisation standard set by Sanders and Severance 15 . Deviations were mapped between each cast and a direct scan of the participant's residual limb, and between the pairs of repeat manual casts and scans.…”
Section: Methodsmentioning
confidence: 99%
“…Rectification maps such as those calculated in this study have been used to compare consistency of cast rectifications between prosthetists, 24 build CAD–CAM templates, 2,3,25 and assess CAM sockets. 4,5 As proposed by Sidles et al, 18 rectification maps can also be used as a tool to teach prosthetists how to modify a positive mold for specific socket designs. Additionally, Sidles et al 18 noted that the alignment used to compute rectification maps is convention-dependent: choose the alignment that minimizes the amount of material added or removed or choose an alignment that preserves anatomic landmarks known to be invariant (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…1 With the advent of computer-aided design–computer-aided manufacturing (CAD–CAM), rectifications can also be accomplished by digitally manipulating either a scan of the residual limb or a scan of the negative mold of the residual limb. 15 In either case, rectifications are performed in a manner specific to each socket design.…”
Section: Introductionmentioning
confidence: 99%